Limiting the valence: advancements and new perspectives on patchy colloids, soft functionalized nanoparticles and biomolecules. Issue 30 (20th July 2017) - Bianchi, Emanuela; Capone, Barbara; Coluzza, Ivan; Rovigatti, Lorenzo; van Oostrum, Peter D. J.
Abstract : Artistic representation of limited valance units consisting of a soft core (in blue) and a small number of flexible bonding patches (in orange). Abstract : Limited bonding valence, usually accompanied by well-defined directional interactions and selective bonding mechanisms, is nowadays considered among the key ingredients to create complex structures with tailored properties: even though isotropically interacting units already guarantee access to a vast range of functional materials, anisotropic interactions can provide extra instructions to steer the assembly of specific architectures. The anisotropy of effective interactions gives rise to a wealth of self-assembled structures both in the realm of suitably synthesized nano- and micro-sized building blocks and in nature, where the isotropy of interactions is often a zero-th order description of the complicated reality. In this review, we span a vast range of systems characterized by limited bonding valence, from patchy colloids of new generation to polymer-based functionalized nanoparticles, DNA-based systems and proteins, and describe how the interaction patterns of the single building blocks can be designed to tailor the properties of the target final structures.